Creative Diversity: Promoting Interculturality in Australian Pathways to Higher Education - Allen, Suzanne (Journal of International Students, 2018)
The growth in international student enrollments in Australian pathways to higher education over the last decade is helping to broaden awareness of the presence of culturally diverse ontological perspectives. Nevertheless, tutors and students are still confronted with numerous difficulties that point to an inherent Western denial of cultural differences, of multiple identity formation, such as ethnicity, gender, class and race, and these processes of denial are stultifying the development of intercultural understanding. Methodologies that acknowledge multiplicities, however, may facilitate inclusive pedagogies and deepen interculturality. This essay addresses current problematic performances in Australian pathway contexts, both in policy implementation and pedagogical methodologies, and outlines how support for both diversity and collaboration against hegemonic practices may serve to promote interculturality.